Control of postharvest green and blue molds of lemons with potassium phosphite and hydrogen peroxide, 2011. - Cerioni, Luciana (2012)
Significant losses can occur after the harvest during the storage and marketing of citrus fruit in California due to green and blue molds, caused by P. digitatum and P. italicum, respectively. Currently, both diseases are controlled by application of the fungicides imazalil, sodium ortho-phenyl phenate, pyrimethanil, or thiabendazole.